Quality of Service and Brand Trust Against Decisions Using Indihome in Ciputat Area of South Tangerang - Santoso, Senen; Wulandari, Siswi (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2021)
The purpose of this study is to know the influence between sales promotion to purchase decisions, to know the influence between the quality of service to purchasing decisions, to know the influence between brand trusts on purchasing decisions. The analysis method used is multiple linear regression using SPSS 25 analysis tool. The object of the research in this study was indihome customers of Ciputat region as many as 100 people with random sampling techniques (probability sampling). The results of the analysis stated that partially sales promotion affects purchasing decisions, partially the quality of service services affects purchasing decisions and partially brand trusts affect purchasing decisions, simultaneously (sales promotion, service quality and brand trust) affect purchasing decisions. Concluded in this study is sales promotion influences the decision to use Indihome, the quality of service influences the decision to use Indihome, brand trust influences the decision to use Indihome, simultaneously the promotion of sales of services and brand trust influences the decision to use Indihome.